Spray-flame synthesis of BaTi1-xZrxO3 nanoparticles for energy storage applications. Issue 9 (15th June 2020) - Tarasov, A.; Shvartsman, V.V.; Shoja, S.; Lewin, D.; Lupascu, D.C.; Wiggers, H.
Abstract: BaTi1- x Zr x O3 nanoparticles ( x = 0, 0.05, 0.1, 0.15, 0.2) were successfully produced by the spray-flame synthesis method. The as-synthesized powders are characterized by small (~10 nm) particle sizes as shown by TEM images. The as-synthesized powders were pre-heated at 800 °C to remove organic residuals from the surface. Pellets were then pressed and sintered at 1100 °C for 3 h. XRD measurements of the sintered materials show that the crystallite size decreases with increasing Zr concentration, which was additionally confirmed by TEM. Dielectric measurements show that the Curie temperature shifts towards lower temperatures with increasing Zr concentration accompanied by a decrease in the dielectric permittivity values which is attributed to a decreasing crystallite/particle size. In addition, a frequency dispersion of the permittivity values is discovered. This is mostly ascribed to Maxwell-Wagner polarization effects typical for nanograined ceramics.